Melanin-based plumage coloration is associated with exposure in tawny owls under novel conditions - Perrault Charlotte; Morosinotto Chiara; Brommer Jon E; Karell Patrik (SPRINGER, 2025)
Abstract: Intraspecific color variation is often associated with camouflage or protection, but melanin-based color variation is also linked to behavioral and physiological aspects including boldness. In the melanin-based plumage color polymorphic tawny owl (Strix aluco), the grey morph is known to be more cryptic than the brown morph. Using 19 captive tawny owls (11 grey and 8 brown), we tested if these two color morphs that differ in camouflage tend to differently use exposed perches in a familiar environment (home aviary) and a novel environment (experimental aviary), as well as whether their response to predation risk and mobbing cues differs. The two color morphs did not differ in their exposure under known conditions (in their home aviary), but brown tawny owls were more likely to use exposed perches than grey tawny owls after release in a novel environment.
Significance statement: Melanin-based coloration can be associated with several behavioral traits. However, it is still unknown how predators with genetically-based color polymorphism vary in their efficiency of active background choice and risk-prone behavior while facing predation risk or mobbing harassment. Using captive tawny owls, we investigated predators' behavior (attention towards the stimulus and use of space) while confronted to mobbing events and predation risk. We showed that tawny owls were using their space differently according to their color morph in a novel environment (experimental aviary) but not in a familiar environment (home aviary).